Built environment & crime prevention: development & issues / Mohamed Yusoff Abbas - Abbas, Mohamed Yusoff (2004)
Reducing crime in the built environment would certainly add to an improved quality of life, but are efforts being made to achieve this goal? Who should be responsible if the environment designed or created is unsafe? This article briefly traces the development and related issues on the study of crime prevention through design of the built environment. It culminates with an important cautionary note on the legal responsibility of those currently involved with the creation of the built environment.